Conceptual framework on moderating effects of psychology factors for stewardship of sustainable behaviours - Yoong, Siew Wai; Bojei, Jamil (2015)
Empirical research and opinion polls make it evident that environmental awareness, consciousness and concerns are highly registered, and pro-environment behaviour adoption is the function of the said factors; moreover marketers are active to adopt pro-environmental marketing strategies and environmental appeals to contribute in addressing these environmental issues. However, various symptoms, such as licensing and rebound effects signifies pro-environmental behaviours are not sustained in different spatial and temporal dimensions, and does not spill over to a wide range of activities, resultant of minute improvements on the environment. Thus, this study aims to expand the knowledge domain by examining the moderating effect of individuals’ psychology factors on attitude-sustainable behaviours relationship, and subsequently in sustaining the consistency of attitude-sustainable behaviours relations. The overriding research objective is twofold, (i) to examine the moderating effects of personal characteristics (age, gender and education) as a social stimulus in diffusing sustainable behaviours, and (ii) to identify factors to sustain attitude-sustainable behaviours relationship. Through the understanding of latent factors that drive sustainable behaviours, it will provide insights for various stakeholders in enhancing managerial discretion, or latitude of action, coupled with concomitantly greater organisational variety for more pronounced and sustainable behaviours ecologically, culturally, socially, economically and politically.